Prey species and abundance affect growth and photosynthetic performance of the polyphagous sea slug Elysia crispata - Paulo Cartaxana; Luca Morelli; Elena Cassin; Vesa Havurinne; Miguel Cabral; Sónia Cruz (Royal Society Open Science, 2023)
Some sacoglossan sea slugs steal functional macroalgal chloroplasts (kleptoplasts). In this study, we investigated the effects of algal prey species and abundance on the growth and photosynthetic capacity of the tropical polyphagous sea slug Elysia crispata. Recently hatched sea slugs fed and acquired chloroplasts from the macroalga Bryopsis plumosa, but not from Acetabularia acetabulum. However, adult sea slugs were able to switch diet to A. acetabulum, rapidly replacing the great majority of the original kleptoplasts. When fed with B. plumosa, higher feeding frequency resulted in significantly higher growth and kleptoplast photosynthetic yield, as well as a slower relative decrease in these parameters upon starvation. Longevity of A. acetabulum-derived chloroplasts in E. crispata was over twofold that of B. plumosa. Furthermore, significantly lower relative weight loss under starvation was observed in sea slugs previously fed on A. acetabulum than on B. plumosa. This study shows that functionality and longevity of kleptoplasts in photosynthetic sea slugs depend on the origin of the plastids. Furthermore, we have identified A. acetabulum as a donor of photosynthetically efficient chloroplasts common to highly specialized monophagous and polyphagous sea slugs capable of long-term retention, which opens new experimental routes to unravel the unsolved mysteries of kleptoplasty.